(untitled) (Journal of Hama University, 2022)
Support luteal function is considered as the most important thing contribute in raising reproduction efficiency in farm animals. This study was designed to know the effect of buserelin administration, Post mating in Shami goats,18 shami.goats were synchronizing estrus with vagina sponge for 11 day,75 mcg of cloprostinol and 150 IU of (ecG) were administered 48 h before sponge removal, then the were mated 48 h post sponge removal, then the does were divided randomly in two group ( 9 does in each group) and treat group was injected i.m.1ml Buserelin acetate ( ) on day 12 post mating,control group was inected 1 ml i.m.normal saline. The result of ultrasound scan show pregnancy test 45 and 90 day showed pregnancy rate (77.77-66.66) % then kidding rate (77.77-66.66) % and twin rate (71.42-66.62)% in treat group and control group respectively, this study concluded that buserelin injection on day 12 post mating has positive effect in reproduction efficiency bookmarks in shami goats.